2021
DOI: 10.1021/acs.macromol.0c02424
|View full text |Cite
|
Sign up to set email alerts
|

Role of Molecular Architecture on Ion Transport in Ethylene oxide-Based Polymer Electrolytes

Abstract: This work aims to develop a detailed mechanistic understanding of the role of a graft polymer architecture on lithium ion (Li+) transport in poly­(ethylene oxide)-based polymer electrolytes. Specifically, we compare Li+ transport in poly­(ethylene oxide) (PEO) versus poly­(oligo oxyethylene methacrylate) (POEM) polymers doped with lithium bis­(trifluoromethanesulfonyl) (LiTFSI) salts, using both experimental electrochemical characterization and molecular dynamics (MD) simulations. Our results indicate that POE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 72 publications
2
77
0
Order By: Relevance
“…On the other hand, OE side chains are well known to be Li +ion conductors in disordered form. 81,82 Because doping is not able to induce significant crystallinity in the high OE fraction samples, we find that the ionic conductivity shows an opposite trend compared to the electronic conductivity. Higher OE fraction samples are the most disordered and thus show higher ionic conductivity.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…On the other hand, OE side chains are well known to be Li +ion conductors in disordered form. 81,82 Because doping is not able to induce significant crystallinity in the high OE fraction samples, we find that the ionic conductivity shows an opposite trend compared to the electronic conductivity. Higher OE fraction samples are the most disordered and thus show higher ionic conductivity.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…PEO has a flexible macromolecular chain, which benefits Li + transport [17]. Several Li + transport pathways have been observed in simulation studies, such as Li + moving along the PEO chains, Li + complexing and decomplexing with anions, and Li + occasionally hopping between the adjacent PEO chains [18], [19], [20]. Borodin et al [15] showed that Li cations moving along the PEO chains generally show stronger mobility than those that jump between the PEO chains, suggesting that enhancing the movement along the PEO chains can significantly promote Li + diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…[42,43] With regard to brush polymers, simulation studies found that the middle of the side chains offer more permutations to form the contiguous six or three EO solvating segments to complex Li + , whereas the positions near the backbone and side chain tails share the less solvation probability. [44,45] As a result, the polymer brush with shorter side chain length, especially with 350 Da or less that holds only a few EO units, has lower fraction of effective solvation sites, leading to a decrease of c. Synergistically, the enhancement of μ and c results in the increased ionic conductivity with the side chain length.…”
Section: Resultsmentioning
confidence: 99%